Genome-wide transcriptome analysis using RNA-Seq reveals a large number of differentially expressed genes in a transient MCAO rat model - Dergunova, Lyudmila V. (BMC Genomics, 2018)
BACKGROUND: The transient middle cerebral artery occlusion (tMCAO) model is used for studying the molecular mechanisms of ischemic damage and neuroprotection. Numerous studies have demonstrated the role of individual genes and associated signaling pathways in the pathogenesis of ischemic stroke. Here, the tMCAO model was used to investigate the genome-wide response of the transcriptome of rat brain tissues to the damaging effect of ischemia and subsequent reperfusion. RESULTS: Magnetic resonance imaging and histological examination showed that the model of focal ischemia based on endovascular occlusion of the right middle cerebral artery for 90 min using a monofilament, followed by restoration of the blood flow, led to reproducible localization of ischemic damage in the subcortical structures of the brain. High-throughput RNA sequencing (RNA-Seq) revealed the presence of differentially expressed genes (DEGs) in subcortical structures of rat brains resulting from hemisphere damage by ischemia after tMCAO, as well as in the corresponding parts of the brains of sham-operated animals. Real-time reverse transcription polymerase chain reaction expression analysis of 20 genes confirmed the RNA-Seq results. We identified 469 and 1939 genes that exhibited changes in expression of > 1.5-fold at 4.5 and 24 h after tMCAO, respectively. Interestingly, we found 2741 and 752 DEGs under ischemia–reperfusion and sham-operation conditions at 24 h vs. 4.5 h after tMCAO, respectively. The activation of a large number of genes involved in inflammatory, immune and stress responses, apoptosis, ribosome function, DNA replication and other processes was observed in ischemia–reperfusion conditions. Simultaneously, massive down-regulation of the mRNA levels of genes involved in the functioning of neurotransmitter systems was recorded. A Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis showed that dozens of signaling pathways were associated with DEGs in ischemia–reperfusion conditions. CONCLUSIONS: The data obtained revealed a global profile of gene expression in the rat brain sub-cortex under tMCAO conditions that can be used to identify potential therapeutic targets in the development of new strategies for the prevention and treatment of ischemic stroke. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-018-5039-5) contains supplementary material, which is available to authorized users.